Internet Addiction and Antisocial Internet Behavior of Adolescents - Hing Keung Ma (The Scientific World Journal)
Internet addiction and the moral implication of antisocial Internet behavior will be investigated in this paper. More and more people use the Internet in their daily life. Unfortunately the percentage of people who use the internet excessively also increases. The concept of Internet addiction or pathological use of Internet is discussed in detail, and the characteristics of Internet addicts are also delineated. The social (especially the antisocial) use of Internet is discussed. It is argued that the behavior of Internet use is similar to daily life social behavior. In other words, Internet behavior is a kind of social behavior. Kohlberg's theory of moral development is employed to delineate the moral reasoning of the antisocial Internet behavior. The following behaviors are regarded as antisocial Internet behavior: (1) the use of Internet to carry out illegal activities such as selling faked products or offensive pornographic materials, (2) the use of Internet to bully others (i.e., cyberbullying) such as distributing libelous statements against a certain person, (3) the use of Internet to cheat others, and (4) the use of Internet to do illegal gambling. The characteristics of the moral stages that are associated with these antisocial Internet behaviors are investigated in detail.